Peran dan Fungsi Petugas Kesehatan Dalam Menjaga Kesejahteraan Dan Kesehatan Reproduksi Ibu Melalui Program Keluarga Berencana - Adam, Jeanne d'Arc Zafera; Betan, Abu Bakar; Nuryani, Siti; Wijayanti, Lumastari Ajeng; Mildaratu, Mildaratu (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Health workers in the midwife profession are at the forefront in maintaining the welfare and reproductive health of women so that midwives have a very important role, one of which is making the family planning program launched by the government a success. Of course midwives cannot work alone, midwives must collaborate with other related parties. Implementation of community service activities aims to carry out the duties of midwives in making family planning activities a success. The methods used are lectures and discussions as well as providing and installing long-term contraceptives, namely intrauterine devices and implants. Implementation of activities at the Community Health Center and for the results of knowledge and understanding related to welfare and maintaining women's reproductive health through family planning and the results of the provision and installation of long-term contraceptive devices, implants in the new installation category amounted to 30.91% and in the dismantling category amounted to 34.55%, while intrauterine contraceptives in the newly installed category were 18.18% and in the removable category were 16.36%. The conclusion that can be drawn is that midwives have carried out their role in the family planning program launched by the government. PUS has had a shift in thinking in planning family size to choose long-term contraceptives.